One vaccine to counter many diseases? Modeling the economics of oral polio vaccine against child mortality and COVID-19 - Chang, Angela Y.; Aaby, Peter; Avidan, Michael S.; Benn, Christine S.; Bertozzi, Stefano M.; Blatt, Lawrence; Chumakov, Konstantin; Khader, Shabaana A.; Kottilil, Shyam; Nekkar, Madhav; Netea, Mihai G.; Sparrow, Annie; et al. (Frontiers in Public Health, 2022)
Introduction Recent reviews summarize evidence that some vaccines have heterologous or non-specific effects (NSE), potentially offering protection against multiple pathogens. Numerous economic evaluations examine vaccines' pathogen-specific effects, but less than a handful focus on NSE. This paper addresses that gap by reporting economic evaluations of the NSE of oral polio vaccine (OPV) against under-five mortality and COVID-19. Materials and methods We studied two settings: (1) reducing child mortality in a high-mortality setting (Guinea-Bissau) and (2) preventing COVID-19 in India. In the former, the intervention involves three annual campaigns in which children receive OPV incremental to routine immunization. In the latter, a susceptible-exposed-infectious-recovered model was developed to estimate the population benefits of two scenarios, in which OPV would be co-administered alongside COVID-19 vaccines. Incremental cost-effectiveness and benefit-cost ratios were modeled for ranges of intervention effectiveness estimates to supplement the headline numbers and account for heterogeneity and uncertainty. Results For child mortality, headline cost-effectiveness was 650 per child death averted. For COVID-19, assuming OPV had 20% effectiveness, incremental cost per death averted was 23,000–65,000 if it were administered simultaneously with a COVID-19 vaccine <200 days into a wave of the epidemic. If the COVID-19 vaccine availability were delayed, the cost per averted death would decrease to 2600–6100. Estimated benefit-to-cost ratios vary but are consistently high. Discussion Economic evaluation suggests the potential of OPV to efficiently reduce child mortality in high mortality environments. Likewise, within a broad range of assumed effect sizes, OPV (or another vaccine with NSE) could play an economically attractive role against COVID-19 in countries facing COVID-19 vaccine delays. Funding The contribution by DTJ was supported through grants from Trond Mohn Foundation (BFS2019MT02) and Norad (RAF-18/0009) through the Bergen Center for Ethics and Priority Setting.